2014
DOI: 10.17221/7191-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the optimal ratio of standardized ileal digestible tryptophan to lysine for finishing barrows fed low protein diets supplemented with crystalline amino acids

Abstract: Optimum standardized ileal digestible (SID) tryptophan (Trp) to lysine (Lys) ratio was estimated for 67-96 kg barrows fed low protein diets supplemented with crystalline amino acids (AA). One hundred and fifty Yorkshire × Landrace barrows, with an average initial body weight (BW) of 67.3 ± 3.2 kg, were used in a 28-day feeding trial. All dietary treatments were based on corn, wheat bran, and soybean meal and were formulated to provide 10.5% crude protein and 12.6 MJ/kg metabolizable energy. The dietary SID Lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…However, the requirement was better estimated using the quadratic model than the linear broken-line model. In accordance with this result, both Gaines et al (2011), in estimating the SID Val:Lys ratio of 13-to 32-kg pigs, and Xie et al (2014), in estimating the SID Trp:Lys ratio of finishing barrows, found that the requirements were higher using a quadratic model than a linear broken-line model.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, the requirement was better estimated using the quadratic model than the linear broken-line model. In accordance with this result, both Gaines et al (2011), in estimating the SID Val:Lys ratio of 13-to 32-kg pigs, and Xie et al (2014), in estimating the SID Trp:Lys ratio of finishing barrows, found that the requirements were higher using a quadratic model than a linear broken-line model.…”
Section: Discussionsupporting
confidence: 75%
“…The SUN concentration can be an indirect indicator of the AA balance in the diet, as a lower SUN indicates a reduced need for deamination and improved AA balance in the diet (Htoo et al, 2014). Therefore, SUN has been used as a rapid response criterion to estimate AA requirements of pigs (Coma et al, 1995;Xie et al, 2014). The SID Val:Lys ratios estimated in Exp.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the reported SID Lys requirement (10.3 g/kg SID Lys) for growing pigs (22–50 kg) (Lu, ) and (7.5 g/kg SID Lys) for finishing pigs (72–100 kg) (Xie et al., ) fed with low CP diets were higher than that of the NRC () values. Likewise, the ideal ratios of SID Thr:Lys and SID Trp:Lys for growing pigs (Zhang et al., , ) and finishing pigs (Xie et al., , ) fed with low CP diets were also higher than the NRC () recommendation. Nutrient requirement estimates can be affected by the regression method used (Kendall et al., ; Pesti, Vedenov, Cason, & Billard, ).…”
Section: Discussionmentioning
confidence: 97%
“…Amino acids in the plasma were analyzed by an automatic amino acid analyzer (S433D, Sykam GmbH, Eresing, Germany) according to Xie et al [16] with minor modifications. Briefly, 1 mL of plasma and salicylsulfonic acid (2%) were mixed thoroughly and then placed in an ice bath for 15 min.…”
Section: Plasma Amino Acid Analysismentioning
confidence: 99%